Avaliação da qualidade nutricional e funcional do óleo de murici (Byrsonima crassifólia L.) - SANTOS, Mayara Priscila Lima dos (2023)
Brazil has one of the largest fruit diversity in the world, but many fruits are still little explored, however these species present a high nutritional value, functional and specific sensorial characteristics. therefore, the objective of the research was to evaluate the nutritional and functional antithrombogenic, antiinflammatory and hypocholesterolemic profile of muruci oil (Byrsonima crassifolia L.). The methodological bases and methods applied followed the internationally accepted standard procedures in food analysis by the Association of Official Analytical Chemists (AOAC). From the results obtained, the oil had a lipid content of 12.32% and a considerable value of carotenoids averaging 490.69 μg.100g1 in the fruit pulp. The result of the chromatographic profile of the Muruci oil presents as major constituents the acid oleic acid with 45.7% and linoleic acid with 15.3%, linolenic acid is present, but in a small amount about 0.015%. From the quality index of the lipid fractions of the murici oil we obtain the following results: Atherogenicity index: 0.47; Thrombogenicity index: 1.05 and Hipo / Hypercholesterolemic ratio: 1.91. In view of this it was possible to conclude that muruci oil has a great nutritional and functional potential. The presence of a lipid profile consisting mainly of unsaturated fatty acids of the omega series (ω9, ω6 and ω3) shows Muruci oil to be of considerable relevance in the prevention of cardiovascular diseases with antithrombogenic, inflammatory and hypocholesterolemic.